TINJAUAN YURIDIS TERHADAP PUTUSAN HAKIM DALAM PENJATUHAN HUKUMAN BADAN SEBAGAI PENGGANTI DALAM PEMBAYARAN UANG PENGGANTI DALAM PERKARA TINDAK PIDANA KORUPSI - Bobbi Sandri; Mahmud Mulyadi; Muhammad Hamdan; Hasim Purba (USU LAW JOURNAL, 2016)
ABSTRACT Regulation of punishment is found in other laws. The Penal Code does not limit punishment to the Law No. 31/1999, for example, regulates other punishments such as compensation for the corrupted; the additional punishment is indemnification. This principle is found in some regulations in the Penal Code. Article 38, paragraph 5 states that a defendant dies and evidence has done, the judge orders to confiscate the defendant’s objects.  The legal corporal punishment is found in Article 10 of the Penal Code. Judge’s punishment as the compensation for paying indemnity has two reasons: judicial reason and non-judicial reason in the Penal Code. When a defendant case dies before the alternative punishment is implemented, it is regulated in No. 31/1999  jo No. 20/2001 obtained through civil procedure and criminal procedure. Law enforcement, the prosecutor and the judge, should sue and decide to punish the perpetrators in corruption punishment by returning the assets to the State. More specific regulation should be implemented on returning the State’s assets in corruption case when the defendant dies prior to the corporal punishment in the judge’s verdict which is final and binding. Regulation should be carried out in the criminal law and regulate criminal responsibility to the corporal punishment as the compensation. Keywords: Corporal Punishment, Compensation, Corruption Case